Meningkatkan Keterampilan Mengolah Ikan Teri Melalui Metode Proyek Bagi Anak Tunagrahita Ringan di SLB BINAR Tarusan - Etmita, - Yosfan Azwandi (Universitas Negeri Padang, 2013)
The background of this research is the result of six people found mild mental retardation students of class VII/C SLB Binar Tarusan who have difficulty in following the fish processing skills lessons. This is because the classroom teachers deliver the subject matter has not been performed in accordance with the process of learning steps anchovy. So far, only the teacher demonstration method in providing skills subjects, thus making students often forget or become less understand what the teacher explained. By the time the fish processing children have difficulty doing salting, boiling, and separation. The purpose of this research is to improve fish processing skills through the project method for mild mental retardation children of class VII/C. This pebelitian type is action research class (classroom action research) that takes the form of collaboration.